(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
Climate change and the finite nature of traditional electricity production sources have resulted in the increasing utilization of renewable electricity sources in today’s electricity grid architecture. Which is hoped to eventually lead to a hundred percent renewable electricity grid architecture. A purely renewable electricity grid will bring about the implementation of the Internet of Renewable Energy (IoRE). The European Union (EU) in an attempt to stimulate and strengthen the integration of electricity grid architecture of member states has set in motion several strategies. A great strategy should be a purely renewable electricity grid assets integration in the region. Besides hydro and wind energy, bioenergy is following on the listing of vital renewable energy sources consumed in the European electricity generation mix. Bioenergy electricity combined with other renewables on the IoRE framework will lead to a sustainable electricity grid integration in the EU. The anticipated utilization of IoRE technology in the short-term and long-term in the region will lead the way to assess a hundred percent renewable electricity product by consumers in each member country. It will as well bring about cleaner electricity product production in the EU.